2020
DOI: 10.1002/jobm.202000035
|View full text |Cite
|
Sign up to set email alerts
|

Simple methods to remove microbes from leaf surfaces

Abstract: Endophytes have been defined as microorganisms living inside plant tissues without causing negative effects on their hosts. Endophytic microbes have been extensively studied for their plant growth-promoting traits. However, analyses of endophytes require complete removal of epiphytic microorganisms. We found that the established tests to evaluate surface sterility, polymerase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Recently, Saldierna Guzmán et al . (2020) performed a comparison of leaf sterilization protocols for two species, an angiosperm and a gymnosperm. They found that complete removal of the cuticle was required to achieve the sterilization of leaf surface in both species, but that the most effective reagents to remove the cuticle without damaging the integrity of leaf tissues differed between species.…”
Section: Methodological Challenges and Limitations To Study Endophytesmentioning
confidence: 99%
“…Recently, Saldierna Guzmán et al . (2020) performed a comparison of leaf sterilization protocols for two species, an angiosperm and a gymnosperm. They found that complete removal of the cuticle was required to achieve the sterilization of leaf surface in both species, but that the most effective reagents to remove the cuticle without damaging the integrity of leaf tissues differed between species.…”
Section: Methodological Challenges and Limitations To Study Endophytesmentioning
confidence: 99%
“…All samples were then surface-sterilized by immersion in 1% NaClO solution prepared with DNA-free autoclaved water for 2 min, 70% EtOH for 2 min and rinsed twice in sterile, DNA-free autoclaved water for 5 min. Surface sterilization is a common and effective technique used to prevent the polymerase chain reaction (PCR) amplification of DNA that is found on the surface of tissues [39][40][41][42][43]. It is considered the gold standard [44] and the application of bleach NaClO ensures DNA is denatured [45,46].…”
Section: Methodsmentioning
confidence: 99%
“…All samples were rinsed in 0.2 μm filtered water collected from the river and, sediment-free tissues were then immerged in 70% ethanol for 30 s followed by a rinse in sterile Milli-Q water (MoBio Laboratories, Carlsbad, CA, United States). This procedure was repeated three times, with a final rinse in Milli-Q water performed three times to remove any excess of ethanol ( Saldierna Guzmán et al, 2020 ). Fruits were surface sterilised as described above prior to opening with a sterilised razor blade in order to remove the seeds.…”
Section: Methodsmentioning
confidence: 99%